Kewarganegaraan dalam Tinjauan Sosial : Integrasi Sosial Warga Negara Asing di Indonesia - Ahmad Muhamad Mustain Nasoha; Anita Rini Febriyanti; Khoirun Nisa Mutmainah; Mohammad Ulil Abshor Abdalla; Rohanifah Fitriana Devi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research focuses on the social integration of foreign nationals in Indonesia from the perspective of citizenship. Indonesia has become a favored destination for many foreigners who come to work, study, or seek refuge due to the increasing global mobility. However, the social integration process of foreign nationals in Indonesia faces several challenges, including restrictive citizenship policies and significant cultural and social differences. The aim of this study is to examine the factors that influence the social integration of foreign nationals in Indonesia and to provide policy recommendations that could facilitate a better integration process. This study employs a qualitative case study approach. Policy analysis, in-depth interviews with foreign nationals and local communities, as well as literature reviews from various sources, are all part of the process. The research findings indicate that Indonesia's strict citizenship policies, along with a lack of understanding and interaction between foreign nationals and local communities, are often major barriers to the integration process. The extent to which foreign nationals can integrate into society is influenced by access to education and employment, as well as community support. Additionally, the study compares the social integration processes of foreign nationals in Indonesia with those in countries such as the United States, Germany, and Australia; it was found that more inclusive policies and better-organized integration programs play a significant role in the success of foreign nationals' integration in these countries.